1998
DOI: 10.1007/s005350050083
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the colon: Report of a case and review of the literature

Abstract: We report a case of carcinosarcoma in the transverse colon in a 60-year-old woman. She was admitted to our hospital for further examination of occult blood in October, 1995. Colonoscopy disclosed an elevated lesion with ulceration in the transverse colon, and she underwent right hemicolectomy. Histopathological examination revealed the tumor to consist of both carcinomatous and sarcomatous elements, the latter being more predominant. Immunohistochemistry revealed vimentin immunoreactivity in most of the sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…Three patients died of the tumor within a year. The best predictors of outcome in sarcomatoid carcinoma seem to be tumor location, size, invasion depth, and the clinical stage of the disease (1,(11)(12)(13). The majority of tumors in upper aerodigestive tract including esophagus and stomach have polypoid growth patterns and can be diagnosed early in their course, and accordingly, are associated with a relatively favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients died of the tumor within a year. The best predictors of outcome in sarcomatoid carcinoma seem to be tumor location, size, invasion depth, and the clinical stage of the disease (1,(11)(12)(13). The majority of tumors in upper aerodigestive tract including esophagus and stomach have polypoid growth patterns and can be diagnosed early in their course, and accordingly, are associated with a relatively favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, our search by computer (MED-LINE search) revealed only six cases of the colonic sarcomatoid carcinomas reported (1)(2)(3)(4)(5)(6). As a result, the natural history of these unusual tumors and the best methods of treatment thereof are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…detected one in the descending colon in 1995, it has rarely been reported. Presently, including our case, 23 cases have been reported [1, 3, 4, 8-26] (Table 1). …”
Section: Discussionmentioning
confidence: 76%
“…A carcinosarcoma may develop in many different organs, but most commonly it is found in the head and neck area and in the female reproductive organs. In the gastrointestinal system, a carcinosarcoma occurs in the esophagus, stomach and biliary duct primarily, and it has been rarely reported in the large intestine [1, 3-5]. Generally, a carcinosarcoma has an aggressive behavior and a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Matsusaka et al showed that pseudosarcoma and sarcomatoid carcinoma were histologically and clinically the same conditions [20] . Moreover, several reports have used carcinosarcoma interchangeably to describe sarcomatoid carcinoma, further confusing the diagnosis and classification of these tumors [13,16,21] . Rosai J explained that when the sarcomatous component is mainly composed of spindle cells but still identifiable as epithelial ones morphologically or immunohistochemically, the diagnosis should be called sarcomatoid carcinoma [22] .…”
Section: Discussionmentioning
confidence: 99%